Developmental toxicity of auranofin in zebrafish embryos. Issue 5 (4th November 2016) - Gao, Xiao‐Yan; Li, Kang; Jiang, Ling‐Ling; He, Ming‐Fang; Pu, Cun‐Hai; Kang, Dongzhou; Xie, Jingjing
Abstract: Auranofin (AF) is used in clinic for the treatment of rheumatoid arthritis, repurposing of AF as an anticancer drug has just finished a phase I/II clinical trial, but the developmental toxicity of AF remains obscure. This study focused on its developmental toxicity by using zebrafish embryos. Zebrafish embryos were exposed to different concentrations (1, 2.5, 5, 10 μm ) of AF from 2 h post‐fertilization (hpf) to 72 hpf. At 72 hpf, two major developmental defects caused by AF were found, namely severe pericardial edema and hypopigmentation, when embryos were exposed to concentrations higher than 2.5 μm . Biochemical detection of oxidative stress enzyme combined with expressions of a series of genes related to oxidative stress, cardiac, metal stress and pigment formation were subsequently tested. The superoxide dismutase activity was decreased while malondialdehyde content was accumulated by AF treatment. The expression of oxidative stress‐related genes ( sod1, gpx1a, gst ), pigment‐related genes ( mitfb, trp‐1a ) and one metal stress‐related gene ctr1 were all decreased by AF exposure. The expressions of cardiac‐related genes ( amhc, vmhc ) and one metal‐related gene hsp70 were found to be significantly upregulated by AF exposure. These findings indicated the potential developmental toxicity of AF on zebrafish early development. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In the present study, we described the developmental toxicity of auranofin. The biochemical levels of oxidative stress enzymes as well as the expressions of a series of genes related to oxidative stress, cardiac, metal stress and pigment formation were detected. Our findings may help gain a better insight into the molecular mechanisms underlying AF‐induced development defects.